Profitability of raspberries cultivation - Baranowska, Alicja; Zarzecka, Krystyna (Management and Administration Journal, 2023)
Poland is a major producer of berries, including raspberries. The profitability of growing raspberries depends, not only, on expenses incurred for the annual plantation, but also primarily, on the purchase prices and yields quantity. That is why, currently, in times of a high price volatility and fruit supply the outlays arouse increasing interest among raspberries planters, thus defining the outlays of production determines the basis of economic calculation and the assessment of the business effectiveness. Field experiments were conducted on a commercial plantation with an area of 1.2 hectares between the years 2012–2013. The research material consisted of data regarding the cultivation of an autumn raspberry variety, Polana. The aim of the study was to determine the economic efficiencyof Polana production on the basis of SGM (Standard Gross Margin). The results revealed that the production of raspberries in 2012–2013 was profitable. In the direct cost structure, specific costs were the highest and covered labuor hired for manual harvesting.